Energy optimization based on project life cycle (PLC): a literature review - Aidon Uda Subrata Aditama Kittie; Frieda; Desriantomy; Okta Meilawaty; Supiyan; Devia; Uda Saritha Kittie (E3S Web of Conferences, 2023)
The occurrence of global climate change is caused by the rising temperature of the earth as a result of high CO2 emissions due to excessive energy consumption in the construction sector. Energy consumption in construction activities starts from the pre-construction stage, then the construction stage and finally the post-construction stage. This study aims to find assessment indicators in reducing energy consumption based on literature studies within the scope of the project life cycle (PLC). The method applied here is a qualitative approach by identifying and reviewing some of the literature on reducing energy consumption in construction projects. The literature study found that there are 5 parts in the building life cycle that can be used to identify sources of energy consumption in construction projects, namely the building materials production stage, the construction process, the building use stage, the end of the building's life and disassembly stage. We identified that there are 3 stages of energy calculation in buildings, namely the stages of Manifest Energy, Operational Energy and Demolition Energy. We find that optimizing indirect energy at the production and planning stage has a significant impact on reducing energy consumption at a later stage through building policy and design. While direct energy optimization can be carried out at the construction and operation stages through energy efficiency in each activity.